BIOLOGY OF INSHORE SQUID LOLIGO DUVAUCELLI ORBIGNY, WITH A NOTE ON ITS FISHERY OFF MANGALORE - Rao, G Syda (Indian Journal of Fisheries, 2011)
Loligo duvaucelii is emerging as one of the important components of by-catch of trawl landings atMangalore. Males mature at 124 mm and females around 108 mm. This species spawns from Decemberto May. An analysis of intra ovarian eggs indicated that females spawn only once. In contrast, malesappear to spawn continuously. Females were dominant at length below 150 mm during most of themonths of study. There was a sudden and steep decline in their proportion beyond 150 mm indicatingpost-spawning mortality. The relation between length, ovary weight and fecundity showed good correlation.On an average L. duvaucelii produces about 5,300 eggs. The gonad index and nidamental glandindex were correlated with the maturity of L. duvaucelii. The length-weight relationship between malesand females showed significant difference. The largest recorded male L. duvaucelii was 355 mm andfemale 228 mm, which are highest so far from Indian coasts. A brief account on fishery aspects ofsquids is also presented. There has been a spurt in the squid landings around Mangaiore area.